Limnologia de um sistema integrado tanques-rede e viveiro em fazenda de aquicultura - Sipaúba-Tavares, Lúcia Helena [UNESP]; Millan, Rodrigo Ney; Milstein, Ana (FapUNIFESP (SciELO), 2016)
Aim: Examining whether small-scale tilapia cages have a potential influence on water abiotic parameters in a pond of a flow-through system. Methods: Tilapia cages were installed near the pond water outlet. Samples for determination of abiotic parameters were monthly collected during eight months at five sampling sites: near three inlets receiving effluents from other fishponds (IW12, IW6 and IWM, the latter opening in a macrophyte bed), close to the cages in the open-pond (CC) and close to the water outlet (WO). The data were analyzed using Principal Component Analysis (PCA). Results: The first PCA axis (70% of the data variability) was related to eutrophication and the second axis (20%) to the dependence of nitrifying bacteria on substrate availability. The sampling sites IW12, CC and WO showed high eutrophication levels. The lowest total phosphorus content, total suspended solids, hardness, alkalinity and conductivity and the highest dissolved oxygen were observed in the macrophyte bed area (IWM). Fish cages significantly increased total phosphorus content, conductivity, alkalinity and hardness in relation to the macrophyte bed inlet. Water outlet abiotic parameters were similar to near cage water. Conclusion: The integrated cage-pond technology may be utilized in flow-through systems if incoming water quality (mainly in the site W12) is improved. Cages should be positioned closer to the pond center where it is deeper allowing higher flow-through and dispersion of uneaten feed residues and feces from the cages. This would avoid their deposition beneath cages and reduce their negatives influence on water quality entering the next fishpond (WO), and therefore not impair fish performance.
Limnology of an integrated cage-pond aquaculture farm
Keywords: Cage culture; Integrated culture; Limnological parameters; Nile tilapia